Mediasi Dan Sulh Sebagai Alternatif Terbaik Penyelesaian Sengketa Hukum Keluarga Islam - Fawaiq Sayyaf, R. Tanzil (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
The higher divorce rate in Religious Courts indicates an increase in cases that occur within Islamic families. Especially the issue in the matter of marriage. Religious Courts mostly resolve divorce issues in litigation rather than through peace. The suboptimal application of mediation as an effort to resolve divorce problems is one of the reasons for the high divorce rate in Religious courts. In this study, this article is limited to two main issues; first, what is the concept of mediation and sulh in the settlement of Islamic family law disputes; Second, how to apply mediation and sulh in the settlement of islamic family legal disputes. The benefit of this research is that the public knows more about the concept of alternative or non-court dispute resolution. The purpose of this study is to discuss efforts to resolve Islamic family law disputes through mediation and sulh. Especially the disputes that are the focus of discussion are marital disputes, inheritance disputes and representation. The research method that will be used is the Library Study, which is a literature review of documents, data, reading materials to be studied, and combined with a normative-juridical approach. The results of this study are explained, that 1) The concepts of Mediation and Sulh are literally different but in substance the same, namely both seeking peace in solving problems 2) In the settlement of Islamic legal disputes, both mediation and sulh if optimized properly, then the problems that exist in human life can be resolved in a peaceful and winning way. Mediation and Sulh are looking at the future rather than looking at the past.